Analysis of Hybrid Warfare Elements in the 2023 Asymmetric War between Hamas and Israel - Fahmi, Irfan; Sutanto, Rudy; Ulhaq M, Faiq Dhiya (PT FORMOSA CENDEKIA GLOBAL, 2024)
The conflict between Hamas and Israel has created a complex asymmetric warfare environment, giving rise to elements of hybrid warfare involving both military and non-military tactics. Hybrid warfare is not a new idea. The focus is primarily on the ability to target distant objects and processes through unconventional military methods, especially for state and military functions. Hybrid warfare, known as an asymmetric approach, seeks to achieve major impact using simple methods, such as stopping an enemy's military operations or cutting off public political support. The operational environment of hybrid warfare consists of a series of interrelated areas of conflict, such as military, economic, social, information, diplomatic, trade, science, and technology. Since states involved in hybrid war do so by undertaking centralized actions in all areas of conflict subject to a single goal, it follows that the actions undertaken by states involved in hybrid war must also be centralized in all areas. Hybrid warfare requires both conventional and unconventional instruments of power and means of subversion. This research aims to analyze the elements of hybrid war in the context of an asymmetric war between Hamas and Israel in 2023.